Adult‐onset regurgitation in a dog with an aberrant right subclavian artery: a CT angiographic study. Issue 1 (9th February 2015) - Miller, Rachel; Wilson, Catherine; Wray, Jon; Jakovljevic, Samuel; Tappin, Simon
Abstract : A two‐year‐old Border Collie presented with a three‐month history of regurgitation. Investigation with plain radiography, digital fluoroscopy, endoscopy and CT angiography (CTA) confirmed the presence of an aberrant right subclavian artery causing dorsal oesophageal compression. In this report, CTA was used to depict the anatomy of an aberrant right subclavian vessel and to highlight the importance of this imaging modality to identify the structures involved in a vascular ring. This report also identifies a patient with a congenital vascular ring anomaly presenting with adult‐onset regurgitation, which has been successfully managed with medical treatment.